Al-S?ulh?: dalam Arbritase Tata Hukum Islam Klasik - Agus Salim (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2017)
This paper discusses arbitration in the classical Islamic legal system. The emergence of Islamic financial institutions today not only affect the financial system with shariah lebel only, more than that, the emergence of shariah financial institutions also affect some legal provisions on the settlement of disputes arising from transactions made Islamic financial institutions with their customers. In this paper the authors use the risert library method with the noramatif approach of Islamic law. In classical Islamic law the settlement of non-litigation disputes can be entered through the Shari way, in the process al-S?ulh? para parties may choose to use al-H?akam (referee) or self-negotiate. The peace process by raising al-H?akam in our legal terms is very similar to the process of Arbitration, therefore it is interesting to take the theme of Arbitrage in the classical Islamic law.